Genetic characteristic of coexisting of mcr-1 and blaNDM-5 in Escherichia coli isolates from lesion-bearing animal organs - Xiang, Yungai; Liu, Zengyuan; Yu, Guo; Song, Yuxia; Li, Yan; Geng, Xujing; Ma, Liying; Guo, Junqing; Tan, Li; Chen, Pengju (Frontiers in Microbiology, 2023)
The coexistence of mcr-1 and blaNDM-5 in the plasmid of E. coli has been widely reported and such strains have been mainly isolated from animal and human feces. However, few reports have focused on the genetic diversity of mcr-1-carrying chromosomes and blaNDM-5-carrying plasmids in E. coli isolates from lesion-bearing animal organs. This study investigated the genetic characteristics of chromosome-mediated mcr-1 and plasmid-mediated blaNDM-5 in E. coli isolated from lesion-bearing animal organs. Nine mcr-1- and blaNDM-5-positive E. coli strains (MNPECs) showed extensive drug resistance (XDR). The predominant clonal complexes (CC) mainly belonged to CC156, CC10 and CC165 from the 56 MNEPCs (including nine strains in this study) retrieved from the literature. These strains were widely distributed in China, and originated from pig fecal samples, human stool/urine samples as well as intestinal contents of chicken. Two transconjugants harboring blaNDM-5 gene were also successfully obtained from two donors (J-8 and N-14) and this transfer increased the MIC for meropenem by 256 times. However, conjugative transfer of mcr-1 gene failed. Both J-8 and N-14 strains contained point mutations associated with quinolone resistance and more than three types of AMR genes, including the mcr-1 gene on the chromosome and the blaNDM-5 gene on the IncX3-type plasmid. The genetic structure of mcr-1 located on the chromosome was an intact Tn6330, and blaNDM-5-carrying IncX3-type plasmid was ISAb125-IS5-blaNDM-5-bleO-trpF-tat-cutA-IS26 gene cassette. Moreover, differences between chromosomes included additional partial sequence of phage integrated into host genome and the different genes associated with O-antigen synthesis.